Ketamine reduces the induced spinal p38 MAPK and pro-inflammatory cytokines in a neuropathic rats - Kwon, So-Young; Yeom, Jae Hwa; Joo, Jin-Deok (Korean journal of anesthesiology, 2014)
Neuropathic rats created by spinal nerve ligation are known to show higher levels of p38, c-Jun NH2-terminal kinase, and extracellular signal-regulated kinase p44/42 (ERK 1/2) of the mitogen-activated protein kinases (MAPKs). The authors of this study aimed to understand the effect of ketamine on p38 MAPK and inflammatory responses, as well as its effect on the development of neuropathic pain. The neuropathic rats were prepared by Chung's method with Sprague-Dawley rats. The research was carried out on three groups, a sham-operated group, a neuropathic pain and normal saline (NP + NS) group, and a neuropathic pain and ketamine (NP + Keta) group. The normal saline or ketamine was infused into the neuropathic rats through a mini-osmotic pump implanted in the subcutaneous space. After a week, the quantities of phospho-p38, p38 MAPK and pro-inflammatory cytokines were measured and compared through western blots and reverse transcriptase-polymerase chain reaction. In comparison to the control group, the NP + NS group showed a significant increase of phospho-p38 and p38 MAPK, as well as of the proinflammatory cytokines, tumor necrosis factor α (TNFα), and intercellular adhesion molecule 1 (ICAM1). However, in the NP + Keta group, phospho-p38, p38 MAPK and TNFα and, ICAM1 were reduced in comparison to the NP + NS group. The paw withdrawal threshold test also showed the trend of recovery from the mechanical allodynia in the NP + Keta group. In the development of neuropathic pain, p38 MAPK and inflammatory responses are significantly related, and the use of ketamine reduces p38 MAPK and proinflammatory cytokines. Thus, the adequate use of ketamine could be effective for the prevention and treatment of neuropathic pain following peripheral injury.